“Nivel de conocimientos y actitudes sobre inmunizaciones contra COVID-19 en odontólogos vacunados de La Libertad, 2021” - Espejo Zuñiga, Jorge Oscar (2022)
The main objective of this basic, descriptive, cross-sectional research study was to determine The level of knowledge and attitudes about immunizations against COVID-19 among vaccinated dentists in La Libertad in the year 2021. The research was carried out with the participation of dentists who were members of the Dental College of Peru - La Libertad Region and who were vaccinated against COVID-19.The study sample consisted of a total of 180 dentists from La Libertad who were vaccinated in 2021, of whom 75 were female (41.7%) and 105 were male (58.3%), 78 were under 30 years of age (43.3%), 89 were between 30 and 44 years of age (49.4%), 12 were between 45 and 60 years of age (6.7%), 1 was over 60 years of age (6.7%), and 1 was over 60 years of age (6.4%). 7%), 1 older tan 60 years (0.6%), 67 graduates of public universities (37.2%), and 113 graduates of private universities (62.8%), 69 with a graduation time of up to 5 years (38.3%), 71 with 6 to 10 years (39.4%), 32 with 11 to 20 years (17.8%) and 8 with more than 21 years since graduation (4.4%). The results indicate that the level of knowledge about immunizations against COVID-19 in vaccinated dentists in La Libertad was 72.8% with a good level, 26.1% with a fair level and 1.1% with a bad level; while the attitude about immunizations against COVID-19 was 98.9% favorable and 1.1% unfavorable.It is concluded that the level of knowledge about immunizations against COVID-19 of the vaccinated dentists of La Libertad in the year 2021 was "good" (72.8%) and the attitudes about immunizations against COVID-19 of the vaccinated dentists of La Libertad in the year 2021 was "favorable" 98.9%.